2014
DOI: 10.1242/jeb.098517
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine regulation of carbonate precipitate formation in marine fish intestine by Stanniocalcin and PTHrP

Abstract: In marine fish, high epithelial bicarbonate secretion by the intestine generates luminal carbonate precipitates of divalent cations that play a key role in water and ion homeostasis. In vitro studies highlight the involvement of the calciotropic hormones PTHrP (parathyroid hormone-related protein) and stanniocalcin (STC) in the regulation of epithelial bicarbonate transport. The present study tested the hypothesis that calciotropic hormones have a regulatory role in carbonate precipitate formation in vivo. Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…It has been well demonstrated that intestinal bicarbonate and calcium concentrations, the substrates required for CaCO 3 formation, are controlled via various mechanisms, which can affect the rate of CaCO 3 formation. Regulators of intestinal bicarbonate include the guanylin peptides 31 and prolactin 32 , where calciotropic hormones such as parathyroid hormone-related protein (PTHrP) and stanniocalcin (STC) can modify both luminal bicarbonate and calcium concentrations 33 34 . Additionally, the presence of calcium itself can modify the rate of intestinal bicarbonate secretion 35 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been well demonstrated that intestinal bicarbonate and calcium concentrations, the substrates required for CaCO 3 formation, are controlled via various mechanisms, which can affect the rate of CaCO 3 formation. Regulators of intestinal bicarbonate include the guanylin peptides 31 and prolactin 32 , where calciotropic hormones such as parathyroid hormone-related protein (PTHrP) and stanniocalcin (STC) can modify both luminal bicarbonate and calcium concentrations 33 34 . Additionally, the presence of calcium itself can modify the rate of intestinal bicarbonate secretion 35 .…”
Section: Discussionmentioning
confidence: 99%
“…There are recent studies that suggest a relationship between calcium transport and HCO 3 − secretion in the intestine of marine fish in terms of regulation by endocrine factors or environmental effects [ 5 , 10 , 23 , 35 , 49 , 50 ]. The single common factor to all studies above cited is calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Drinking is necessary to compensate osmotic water losses [ 1 , 2 , 3 ], therefore water replacement by drinking becomes essential to sustain osmotic regulation [ 4 ]. Several studies have reported the involvement of endocrine and environmental factors in the regulation of the amount of water ingestion by seawater fish [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pufferfish and zebrafish two pth3 were identified and cloned, pth3a/pth3b (Power et al, 2000 ; Canario et al, 2006 ; Yan et al, 2012 ), however only pth3a has been identified in seabream (Flanagan et al, 2000 ). Recent studies have outlined the importance of Pth3 in fish ion balance (Gregório et al, 2014 ). The increase of circulating Pth3 in seabream stimulates the calcium uptake through gills and intestine (Guerreiro et al, 2001 ; Abbink et al, 2006 ; Fuentes and Figueiredo, 2006 ).…”
Section: Pth3 (Pthlh)mentioning
confidence: 99%